Population Pharmacokinetic Modeling of Lenvatinib in Chinese Patients With Advanced Hepatocellular Carcinoma Using Real‐World Data. (12th September 2022) - Hu, Yingying; Chen, Ruijia; Ye, Zhenjie; Wei, Fuqun; Lin, Kecan; Liu, Jingfeng; Zeng, Yongyi
Abstract: Lenvatinib is a novel oral angiogenesis inhibitor approved in China for the treatment of unresectable hepatocellular carcinoma (HCC) without prior systemic treatment. We described the population pharmacokinetics of lenvatinib in Chinese patients with advanced HCC and explore the potential patient characteristics associated with lenvatinib pharmacokinetics using real‐world data. A total of 266 samples, provided by 127 Chinese patients with advanced HCC, were analyzed by nonlinear mixed‐effects modeling. Monte Carlo simulation was conducted to assess impact of covariates on the exposure to lenvatinib. The clearance of lenvatinib in Chinese patients with advanced HCC was 5.3 L/h, and alkaline phosphatase, total bilirubin, and sex were identified as important covariates associated with it. The clearance of Child‐Pugh class B patients (4.82L/h) was significantly lower than that of Child‐Pugh class A patients (5.53 L/h), and the systemic exposure increased with the increase of alkaline phosphatase and total bilirubin. There were sex differences in the pharmacokinetic characteristics of lenvatinib. The clearance of women was significantly lower than that of men (4.61 vs 5.6 L/h; P < .001), and the area under the plasma concentration–time curve of women was ≈20% higher than that of men. In this study, a population pharmacokinetic model of lenvatinib was established, which can be used to simulate clinical trials or various dosing scenarios. Our findings provide important new insights for optimizing the use of lenvatinib in patients with advanced HCC.